A scoping review protocol: Investigating the extent and legal process of cauda equina syndrome claims for UK physiotherapists. (11th March 2021) - Leech, Rachel L.; Selfe, James; Ball, Suzanne; Greenhalgh, Susan; Hogan, Gareth; Holway, Janene; Willis, Emma; Yeowell, Gillian
Abstract: Introduction: Cauda equina syndrome (CES) is a condition where early identification and treatment is crucial to avoid potentially devastating effects. There is a high number of litigation cases linked with CES given it is a relatively rare condition. This scoping review protocol proposes to explore the extent and process of CES litigation in UK healthcare context cases amongst UK physiotherapists. Methods and analysis: The methodological framework recommended by Arksey and O'Malley, Levac et al. and the Joanna Briggs Institute will be used throughout this review to aid reporting and transparency. A patient and public involvement (PPI) group meeting was convened at the beginning of the review process in order to provide knowledge exchange to inform the search strategy and propose resources to be used during the scoping review. Two reviewers will independently review the literature in order to apply the inclusion and exclusion criteria. Once the studies to be included have been identified, the data from these studies will be extracted and charted. Results will show quantitative data of the studies included in the review and a narrative synthesis of the literature. Dissemination: This scoping review will evaluate the existing knowledge relating to CES and litigation and will map the key concepts around this topic. Results will be disseminated to practitioners and policy‐makers through peer‐reviewed publications, conferences, reports and social media. This method may prove helpful to others who are investigating extent and processes relating to medicolegal cases involving healthcare practitioners. Registration: The current paper is registered with OSF registries (DOI 10.17605/OSF.IO/MP6Y3).